Structural abnormalities of the thalamus in juvenile myoclonic epilepsy - Mory, Susana Barreto; Betting, Luiz Eduardo Gomes Garcia [UNESP]; Fernandes, Paula T.; Lopes-Cendes, Iscia; Guerreiro, Marilisa M.; Guerreiro, Carlos A. M.; Cendes, Fernando; Li, Li M. (Academic Press Inc. Elsevier B.V., 2011)
Studies have suggested that the thalamus is a key structure in the pathophysiology of juvenile myoclonic epilepsy. The objective of the present investigation was to examine the thalami of patients with juvenile myoclonic epilepsy using a combination of multiple structural neuroimaging modalities. The association between these techniques may reveal the mechanisms underlying juvenile myoclonic epilepsy and help to identify the neuroanatomical structures involved. Twenty-one patients with juvenile myoclonic epilepsy (13 women, mean age = 30 +/- 9 years) and a control group of 20 healthy individuals (10 women, mean age = 31 +/- 8 years) underwent MRI in a 2-T scanner. The volumetric three-dimensional sequence was used for structural investigation. Evaluation of the thalamus comprised voxel-based morphometry. automatic volumetry, and shape analysis. Comparisons were performed between patient and control groups. Voxel-based morphometry analysis identified areas of atrophy located in the anterior portion of the thalamus. Post hoc analysis of automatic volumetry did not reveal significant differences between the groups. Shape analysis disclosed differences between patients and controls in the anterior and inferior portions of the right thalamus and in the anterior portion of the left thalamus. The present investigation confirms that thalami of patients with juvenile myoclonic epilepsy are structurally abnormal with impairments located mainly in the anterior and inferior sections. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Epilepsy; Neuroimaging; Juvenile myoclonic epilepsy; Magnetic resonance; Volumetry; Voxel-based morphometry